Neurodevelopmental outcome in very preterm and very‐low‐birthweight infants born over the past decade: a meta‐analytic review. (19th January 2018) - Pascal, Aurelie; Govaert, Paul; Oostra, Ann; Naulaers, Gunnar; Ortibus, Els; Van den Broeck, Christine
Abstract : Aim: The purpose of this systematic review was to provide an up‐to‐date global overview of the separate prevalences of motor and cognitive delays and cerebral palsy (CP) in very preterm (VPT) and very‐low‐birthweight (VLBW) infants. Method: A comprehensive search was conducted across four databases. Cohort studies reporting the prevalence of CP and motor or cognitive outcome from 18 months corrected age until 6 years of VPT or VLBW infants born after 2006 were included. Pooled prevalences were calculated with random‐effects models. Results: Thirty studies were retained, which included a total of 10 293 infants. The pooled prevalence of cognitive and motor delays, evaluated with developmental tests, was estimated at 16.9% (95% confidence interval [CI] 10.4–26.3) and 20.6% (95% CI 13.9–29.4%) respectively. Mild delays were more frequent than moderate‐to‐severe delays. Pooled prevalence of CP was estimated to be 6.8% (95% CI 5.5–8.4). Decreasing gestational age and birthweight resulted in higher prevalences. Lower pooled prevalences were found with the Third Edition of the Bayley Scales of Infant Development than with the Second Edition. Interpretation: Even though neonatal intensive care has improved over recent decades, there is still a wide range of neurodevelopmental disabilities resulting from VPT and VLBW births. However, pooled prevalences of CP have diminished over the years. What this paper adds: The Bayley Scales of Infant and Toddler Development, Third Edition reported lower pooled prevalences of motor and cognitive delays than the Second Edition. The pooled prevalence of cerebral palsy in infants born extremely preterm was reduced compared with previous meta‐analyses. What this paper adds: The Bayley Scales of Infant and Toddler Development, Third Edition reported lower pooled prevalences of motor and cognitive delays than the Second Edition. The pooled prevalence of cerebral palsy in infants born extremely preterm was reduced compared with previous meta‐analyses. This article is commented on by Marlow on page330 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.